IMPACT OF SUGAR ALCOHOLS ON ORAL HEALTH – A LITERATURE REVIEW - Michalina Więckowska; Katarzyna Skorupa; Agnieszka Zakrzewska; Karolina Hetmanek; Edyta Szlęzak; Julia Mroczkiewicz; Aleksandra Szczepanik (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: Dental caries is one of the most common chronic diseases worldwide, with sucrose recognized as a key dietary factor in its development. As a result, sucrose substitutes have gained increasing attention as potential tools in caries prevention. Among them, xylitol, sorbitol, and erythritol are the most extensively studied. Xylitol is not fermented by Streptococcus mutans and may help reduce bacterial growth and adhesion. Sorbitol is less cariogenic than sucrose, but can still be slowly fermented by certain microorganisms. Erythritol is not fermented at all and may even help reduce plaque and improve the balance of the oral biofilm.The aim of this study is to summarize what is currently known about sucrose substitutes in relation to oral health, with a particular focus on xylitol, sorbitol and erythritol.Materials and Methods: The review is based on throughout analysis of the materials selected from PubMed, Cochrane and Google Scholar using the following keywords: xylitol, sorbitol, erythritol, sucrose substitutes, sugar alcohols, oral health.Conclusions: The available evidence indicates that xylitol and erythritol are the most beneficial sucrose substitutes for oral health. Erythritol reduces plaque most effectively, inhibits Streptococcus mutans, and slows caries progression, while xylitol lowers bacterial levels with less consistent effects on plaque, and sorbitol is the least protective. To strengthen these findings and develop clear guidelines for polyol use in dentistry, further well-designed long-term trials are necessary.